Two new species of Hemielimaea Brunner von Wattenwyl from China - Wang, Ye-Ying; Ma, Jian-Zhang; Liu, Chun-Xiang (Zootaxa, 2013)
Two new species Hemielimaea (Hemielimaea) paracari sp. nov. and H. (H.) parva sp. nov. from southwestern China are described. Characteristics of the stridulatory file on underside of male left tegmen, male stridulatory area on left and right tegmen, and abdominal apex of male are provided. Important and necessary illustrations of the new species are presented. Materials come from the following two depositories: Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZCAS), and China Agricultural University, Beijing, China (CAU).